Stabilisation of anthocyanins from spray dried hibiscus sabdariffa extracts by encapsulating in different carrier agent - Zuhaili Idham, 1984-; Ida Idayu Muhamad, supervisor; Fakulti Kejuruteraan Kimia dan Kejuruteraan Sumber Asli (2010)
Thesis (Sarjana Kejuruteraan (Bioproses)) - Universiti Teknologi Malaysia, 2010